Alterations of the murine gut microbiome in allergic airway disease are independent of surfactant protein D. Issue 3 (March 2017) - Barfod, Kenneth K.; Roggenbuck, Michael; Al-Shuweli, Suzan; Fakih, Dalia; Sørensen, Søren J.; Sørensen, Grith L.
Abstract: Background: SP-D is an important host defense lectin in innate immunity and SP-D deficient mice show several abnormal immune effects and are susceptible to allergen-induced airway disease. At the same time, host microbiome interactions play an important role in the development of allergic airway disease, and alterations to gut microbiota have been linked to airway disease through the gut-lung axis. Currently, it is unknown if the genotype ( Sftpd-/- or Sftpd+/+ ) of the standard SP-D mouse model can affect the host microbiota to such an degree that it would overcome the cohousing effect on microbiota and interfere with the interpretation of immunological data from the model. Generally, little is known about the effect of the SP-D protein in itself and in combination with airway disease on the microbiota. In this study, we tested the hypothesis that microbiome composition would change with the lack of SP-D protein and presence of allergic airway disease in the widely used SP-D-deficient mouse model. Results: We describe here for the first time the lung and gut microbiota of the SP-D mouse model with OVA induced allergic airway disease. After the challenge animals were killed and fecal samples were taken from the caecum and lungs were subjected to bronchoalveolar lavage for comparison of gut and lung microbiota by Illumina 16S rRNA gene sequencing. A significant community shift was observed in gut microbiota after challenge with OVA. However, the microbial communities were not significantly different between SP-D deficient and wild type mice from the same cages in either naïve or OVA treated animals. Wild type animals did however show the largest variation between mice. Conclusions: Our results show that the composition of the microbiota is not influenced by the SP-D deficient genotype under naïve or OVA induced airway disease. However, OVA sensitization and pulmonary challenge did alter the gut microbiota, supporting a bidirectional lung-gut crosstalk. Future mechanistic investigations of the influence of induced allergic airway disease on gut microbiota are warranted.